New Perspectives : journal of the World Peace Council. - World Peace Council (WPC) (Helsinki, 1976)
Fonds Emilienne Brunfaut
S/92/069A/00Verschijnt tweemaandelijks
Zie ook "Nouvelles perspectives" / Conseil Mondial de la Paix
Engels
Periodiek
Keywords: pacifistische pers; Finland